Pengaruh Kerjasama Tim Terhadap Kinerja Pegawai Di Kantor Kementerian Agama Kabupaten Ogan Komering Ulu Selatan - Nurazizah, Esti Koma; Komaruddin; Hasril Atieq Pohan (Jurnal Kajian Islam dan Sosial Keagamaan, 2024)
This study was conducted to determine the effect of teamwork on employee performance at the Office of the Ministry of Religion of South Ogan Komering Ulu Regency partially. With the aim in the study, namely to determine whether or not there is an influence of teamwork on employee performance at the Office of the Ministry of Religion of South Ogan Komering Ulu Regency. The method used in this research is a quantitative method using a causal associative approach. The data used are primary and secondary data. The data collection techniques used in this research are through observation, questionnaires and Ogan Komering Ulu mentation. The data analysis technique used is simple linear regression analysis. With t test hypothesis testing (partial). The results showed that partially Teamwork has a positive effect on obtaining a tcount value of 3.338> 0.05, it can be concluded that there is a positive influence between Teamwork on employee performance at the Office of the Ministry of Religion of South Ogan Komering Ulu Regency.